Analysis of the Effect of Quick Ratio (QR), Total Assets Turn Over (TATO), and Debt To Equity Ratio (DER) on Return On Equity (ROE) at PT. XYZ - Aniyah; Supriyanto; Kumoro, Dwi Ferdiyatmoko Cahya; Novitasari, Dewiana; Yuwono, Teguh; Asbari, Masduki (Journal of Industrial Engineering & Management Research, 2020)
This study aims to determine the effect of Quick Ratio (QR), Total Assets Turn Over (TATO) and Debt to Equity Ratio (DER) either partially or simultaneously on Return On Equity (ROE) at PT. XYZ for the period 2012-2019. This research is quantitative also includes descriptive and associative causal research. The data of this research are the financial statements of PT. XYZ for the period 2012-2019. The data used are secondary data presented on the Indonesia Stock Exchange (IDX) using financial ratio analysis methods, while the data is processed using the classical assumption analysis test method. The results showed that: There is a positive and insignificant effect between the quick ratio on return on equity as indicated by the t-test result of 1.444 with a significance of 0.159. There is a positive and insignificant influence between total assets turnover on return on equity as indicated by the t-test result of 1.203 with a significance of 0.239. There is a negative and insignificant effect between debt to equity ratio on return on equity, this is indicated by the t-test result of -0.030 with a significance value of 0.977. There is a negative and insignificant effect between quick ratio, total assets turn over and debt to equity ratio on return on equity which is shown from the results of the f-test count of 1.673 with a significance value of 0.195 and can be written with the regression equation ROE (Y) = -880,176 + 0.033 QR (X1) + 0.169 TATTOOS (X2) + 0.022 DER (X3).